2020
DOI: 10.1098/rstb.2019.0646
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of diet-egg transfer of fatty acids in the teleost fish, red drum ( Sciaenops ocellatus )

Abstract: Eggs of marine organisms are increasingly being recognized as important components of marine food webs. The degree to which egg fatty acid profiles reflect maternal diet fatty acid profiles, and therefore the value of fatty acids in eggs as trophic biomarkers, depends on the species' reproductive strategy and the extent of modification of ingested fatty acids. We measured the dynamics of transfer of recently ingested fatty acids to spawned eggs in a batch-spawning teleost, red drum ( Sciaenops ocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…5 NP has been studied on mammals extensively, but early programming in fish is now more researched with several research topics in fish stemming from mammalian studies. 6 NP with PP shows great promise to increase utilization of lower-quality PP sources. 1,5,[7][8][9] Studies have challenged rainbow trout (Oncorhynchus mykiss) with vegetable oil-based diets and reported that the fish later presented higher feed intake, growth, and feed utilization compared to nonprogrammed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…5 NP has been studied on mammals extensively, but early programming in fish is now more researched with several research topics in fish stemming from mammalian studies. 6 NP with PP shows great promise to increase utilization of lower-quality PP sources. 1,5,[7][8][9] Studies have challenged rainbow trout (Oncorhynchus mykiss) with vegetable oil-based diets and reported that the fish later presented higher feed intake, growth, and feed utilization compared to nonprogrammed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, fatty acid compositions of eggs spawned from experimental fish varied among different treatments, and the dominating fatty acid in the egg was 18:1n-9 for whelk meal-incorporated diets, whereas was 22:6n-3 for the control treatment. Fish that reduce or cease feeding during gonadal maturation and spawning mostly obtain necessary lipids from various sources of body including carcass, viscera, abdominal fat, muscle and liver (Fernández-Palacios et al, 2011), and it is reported that a long-term feeding affects fatty acid content of eggs (Hou et al, 2020). For instance, similar studies conducted on rainbow trout (Vassallo-Agius et al, 2001) and Coho salmon (Johnson et al, 2011) indicate an effect of diet on the egg fatty acid composition of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Legacy fatty acids can also be a result of maternal investment of lipids in eggs that feed lecithotrophic larvae and other consumers that prey upon the eggs [46,47]. In this issue, Hou et al [48] capitalized on the deposition of legacy fatty acid in eggs to follow changes in maternal diets. The ideal path is to ensure that the diet fed to the consumer or mother before the experiment begins has a similar composition to both natural diets (if the outcomes are to be applied to natural populations) and the experimental diets in terms of fat content, and is nutritionally balanced and not deficient in essential fatty acids.…”
Section: (D) Legacy Fatty Acidsmentioning
confidence: 99%